Armenias transformative urban future national urban assessmentt. - Asian Devlopment Bank.; Joshi, Kaushal ([Manila] Asian Development Bank, 2019)
The National Urban Assessment for Armenia provides a snapshot of the countrys urban sector and offers insights to achieving prosperous and sustainable cities. Armenia is highly urbanized, with the population concentrated in Yerevan and its surrounding areas given the capital's geopolitical, economic, and cultural legacy.
Keywords: Sustainable development -- Armenia; Economics; Electronic books